Respostas

2014-02-08T16:11:06-02:00
A)    1           x+6          x (x + 6) = 6  ->  x² + 6x =6  ->  x² + 6x - 6 = 0  ->  Δ=b² - 4ac
     ------  =  ---------  ->                          
       x           6                  ----> Δ= 6² - 4.1.(-6)  --->  Δ = 36 + 24  --> Δ = 60

                                                  +                               +
                                -----> x = -b  - √Δ        -->    x = -6  - √2².3.5    -->   x  = -6 + 2√15
                                      ----------------------           ---------------------              ------------------
                                           2.a                               2                                2

      ---> x' = -6 + 2√15      -->  x'' = -6 - 2√15
                 ---------------                -----------------
                       2                              2